The Beginner's Guide to Nation-Building - Dobbins, James (RAND Corporation, 2007)
Since the end of the Cold War, the United States, NATO, the United Nations, and a range of other states and nongovernmental organizations have become increasingly involved in nation-building operations. Nation-building involves the use of armed force as part of a broader effort to promote political and economic reforms, with the objective of transforming a society emerging from conflict into one at peace with itself and its neighbors. This guidebook is a practical Â"how-toÂ" manual on the conduct of effective nation-building. It is organized around the constituent elements that make up any nation-building mission: military, police, rule of law, humanitarian relief, governance, economic stabilization, democratization, and development. The chapters describe how each of these components should be organized and employed, how much of each is likely to be needed, and the likely cost. The lessons are drawn principally from 16 U.S.- and UN-led nation-building operations since World War II and from a forthcoming study on European-led missions. In short, this guidebook presents a comprehensive history of best practices in nation-building and serves as an indispensable reference for the preplanning of future interventions and for contingency planning on the ground.